Salience and Asset Prices - Bordalo, Pedro; Gennaioli, Nicola; Shleifer, Andrei (American Economic Review, 2013)
We present a simple model of asset pricing in which payoff salience drives investors' demand for risky assets. The key implication is that extreme payoffs receive disproportionate weight in the market valuation of assets. The model accounts for several puzzles in finance in an intuitive way, including preference for assets with a chance of very high payoffs, an aggregate equity premium, and countercyclical variation in stock market returns.